Toxicidade aguda do herbicida 2,4-d + picloram em girinos de boana semilineata - Miranda, Deyvid Sousa (Universidade Federal do Tocantins, 2021)
Pesticides are environmental pollutants that can be important causes of mortality of fauna and flora. Environmental pollution by agricultural contaminants has been highlighted and considered one of the factors in the decline of amphibians. Among the herbicides used in pastures, the ones with the active ingredients 2,4-dichlorophenoxyacetic acid (2,4-D) + 4-amino 3,5,6-trichloro-2-pyridinecarboxylic acid (Picloram) in their formulation stand out. Amphibians are one of the fauna groups most threatened with extinction. Among the factors that contribute to their extinction are herbicides, in which their inappropriate use can cause an exacerbated decrease in this group. The objective was to evaluate the acute toxicity of commercial herbicide based on 2,4-D and Picloram in Boana punctata. The experiment used 7 concentrations of 2,4-D + Picloram, commercially known as Norton® (0; 7; 7.5; 8.5; 9; 10; 11; 12 g L-1), with 2 repetitions per treatment with 5 animals each, totaling 70 animals. There is a need to know the influence of pesticides on amphibian communities, so that we can minimize as much as possible the decline of the population of these animals in their habitat. Therefore, from this experiment we determined the values obtained from the toxicological test, which showed 9.49 (g L-1) as the lethal concentration (LC50) of 2,4-D + Picloram. The present study suggests that the application of commercial formulate has the potential to cause significant mortality in tadpoles of Boana semilineata.